Situating instructed language acquisition. Issue 1 (4th July 2017) - VanPatten, Bill
Abstract : What is the relationship between instructed second language acquisition (ISLA) and more general second language acquisition? To what extent is the former informed by the latter? In this essay, I review five facts about second language acquisition involving the nature of mental representation, the slow and ordered acquisition over time, the nature of internal constraints and mechanisms, the role of input, and the observation that most acquisition results in some kind of non-nativeness. I use these facts to ponder underlying assumptions and unasked questions in the research on ISLA. I conclude with some queries regarding the scope and purpose of ISLA.